2021
DOI: 10.1097/cad.0000000000001225
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin inhibits proliferation and migration of psoriatic keratinocytes via the lncRNA NEAT1/miR-3194-5p/Galectin-7 axis

Abstract: To investigate the mechanism underlying the effect of paeoniflorin (PF) on the proliferation and migration of psoriatic keratinocytes. The expressions of long noncoding RNA NEAT1, miR-3194-5p and Galectin-7 in skin tissues from psoriatic patients and healthy controls were detected. Psoriatic HaCat cells were used to investigate the function of NEAT1 and Galectin-7 as well as the effect and mechanism of PF in psoriasis. MTT, colony formation and scratch assays were used to assess the proliferation and migration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…To reflect the heterogeneity of miR‐3194‐5p in CRC cell lines, it is necessary to further detect the effects of miR‐3194‐5p in more types of CRC cells in the future. A previous study demonstrated that PF suppressed psoriatic keratinocyte proliferation and migration by reducing miR‐3194‐5p expression 14 . However, the mechanism and role of miR‐3194‐5p in PF‐mediated anticancer activity for CRC have not yet been elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To reflect the heterogeneity of miR‐3194‐5p in CRC cell lines, it is necessary to further detect the effects of miR‐3194‐5p in more types of CRC cells in the future. A previous study demonstrated that PF suppressed psoriatic keratinocyte proliferation and migration by reducing miR‐3194‐5p expression 14 . However, the mechanism and role of miR‐3194‐5p in PF‐mediated anticancer activity for CRC have not yet been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, PF inhibited CRC cell stemness by repressing the miR‐3194‐5p/CTNNBIP1 axis to inhibit Wnt/β‐catenin signaling activation. Wang et al showed that PF could inhibit the proliferation and migration of psoriatic keratinocytes through the lncRNA NEAT1/miR‐3194‐5p/galectin‐7 axis 14 . Notably, galectin‐7 plays an anticancer role in CRC 35 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations